Policy Influence Debt, Ownership Managerial and Profitability Against Company Value in the Food and Beverages Sub-Sector Indonesian Securities in the 2019-2021 Period - Nicholas; Jonathan Hartanto; Ina Namora Putri Siregar (International Journal Of Economics Social And Technology, 2022)
The purpose of this test is to analyze the effect of debt policy, managerial ownership, and profitability on firm value. there is a decrease in the value of the company due to debt policy, managerial ownership, and unstable profitability. The population in this study was obtained by 39 companies and the sample in this study totaled 25 companies that met the criteria. the research method uses multiple linear regression analysis techniques. The results of testing the hypothesis partially debt policy has a positive effect on firm value, while for managerial ownership and profitability have no effect on firm value. and the simultaneous test results show that the variable debt policy, managerial ownership, and profitability have an influence on the value of food and beverage companies listed on the Indonesia Stock Exchange 2019-2021.